Teaching Pediatric Fellows Palliative Care Through Simulation and Video Intervention: A Practical Guide to Implementation - Katharine Brock; Harvey Cohen; Barbara Sourkes; Julie Good; Kiruthiga Nandagopal; Sylvia Bereknyei Merrell; Louis Halamek (Association of American Medical Colleges, 2015)
Abstract We provide a curriculum for teaching pediatric fellows in critical care, cardiology, hematology/oncology, and neonatology about palliative care, end-of-life care, high-stakes communication, and pain and symptom management. This involves three simulated scenarios with debriefing for each group of fellows and a videotaped palliative care lecture. The resource also includes questionnaires, developed and assessed for reliability and validity that can be used to measure the effectiveness of the curriculum. An external rater training guide is also included so that reviewers of the fellows' videos have criteria with which to measure the fellows' progress and performance. Groups were similar at baseline for demographics, subspecialty, PGY status, and prior palliative care, end-of-life, and patient death experiences Over three months, the intervention (simulation) group significantly improved in self-efficacy (16.4 vs 6.1, Δ 10.3, p = .003) and perceived adequacy of medical education (7.4 vs 0.4, Δ 7.1, p < .001), but not in knowledge (1.1 vs 1.8, Δ −0.7, p = .20). We hypothesized that fellows would peak at the end of day 1 but lose skills over time. However, we saw that skills learned in the intervention group persisted at three months. Compared to the control group, intervention group fellows more strongly agreed that the education was useful (p = .02), would be used in clinical practice (p = .04), and recommended the education (p = .004).